Extracellular Vesicles in Hepatobiliary Malignancies - Lapitz, Ainhoa; Arbelaiz, Ander; Olaizola, Paula; Aranburu, Aitziber; Bujanda, Luis; Perugorria, Maria J.; Banales, Jesus M. (Frontiers in Immunology, 2018)
Primary hepatobiliary malignancies include a heterogeneous group of cancers with dismal prognosis, among which hepatocellular carcinoma (HCC), cholangiocarcinoma (CCA) and hepatoblastoma (HB) stand out. These tumors mainly arise from the malignant transformation of hepatocytes, cholangiocytes (bile duct epithelial cells) or hepatoblasts (embryonic liver progenitor cells), respectively. Early diagnosis, prognosis prediction and effective therapies are still a utopia for these diseases. Extracellular vesicles (EVs) are small membrane-enclosed spheres secreted by cells and present in biological fluids. They contain multiple types of biomolecules, such as proteins, RNA, DNA, metabolites and lipids, which make them a potential source of biomarkers as well as regulators of human pathobiology. In this review, the role of EVs in the pathogenesis of hepatobiliary cancers and their potential usefulness as disease biomarkers are highlighted. Moreover, the therapeutic value of EV regulation is discussed and future directions on basic and clinical research are indicated.